The Role of Empathetic Company Philosophy and Advanced Technologies in Shaping Job Attitudes - Koizumi Masaki; Kato Takumi (Business Systems Research)
Although the literature has assessed various factors underlying employee attitudes, knowledge of company philosophy and advanced technology is lacking, especially in the context of the major drivers of job satisfaction and turnover intentions.